Inhibition of the Citrus Canker Pathogen Using a Photosensitizer Assisted by Sunlight Irradiation - Jiang, Libin; Liu, Yurong; Xu, Xianyuan; Su, Dan; Zou, Huasong; Liu, Jianyong; Yuan, Cai; Huang, Mingdong (Frontiers in Microbiology, 2020)
Citrus canker induced by bacterial infection seriously affects the growth and productivity of citrus around world, and have attracted strong research interest. The current treatment for this disease uses copper salts to inactivate the pathogenic bacteria, Xanthomonas citri subsp. citri (Xcc) strain. However, copper salts may have negative impact to the environment or plant. In this paper, we identify a chemical compound, 2,6-diiodo-1,3,5,7-tetramethyl-8-(P-benzoic acid)-4,4′-¬difluoro¬¬bora¬¬¬dia¬¬zain¬¬dacene (DIBDP), to inactivate the pathogenic Xcc strain (29-1). DIBDP is activated by sunlight and generates reactive oxygen species to kill the bacteria. In order to overcome the degradation of DIBDP under the sunlight, an adjuvant agent was identified to limit the photodegradation of DIBDP by forming a photosensitizer complex (PSC). This complex demonstrated significant antimicrobial activity to Xcc 29-1, which was 64 fold more potent than the copper biocides. The antimicrobial efficacy of PSC on citrus leaves infected by Xcc 29-1 also showed much strong efficacy than copper agent and, at the same time, is safe to the host when exposed to sunlight. Thus, this PSC is a promising antibacterial agent to control citrus canker disease.